PROGRAM PUSAKA SAKINAH SAAT PRA NIKAH : KESADARAN KESETARAAN GENDER DAN KETAHANAN RUMAH TANGGA - M. Asif Nur Fauzi; Khusnul Asma; Moh. Efendi (LPPM Universitas Negeri Surabaya, 2026)
The increasing number of divorce cases filed by women in recent years has become a complex social reality and challenges the construction of family resilience in Indonesia. These divorce cases do not merely reflect a weakening of marital commitment but also demonstrate women's growing awareness of their rights, dignity, and justice in domestic relationships. In this context, the PUSAKA SAKINAH Program, a strategic government effort to strengthen family resilience, faces the challenge of responding to increasingly equal gender relations. This study aims to analyze the challenges of implementing PUSAKA SAKINAH in addressing the phenomenon of divorce cases filed by women from a gender equality perspective. A qualitative approach was used through literature studies, policy analysis, and a review of relevant divorce data. The study results indicate that divorce cases filed by women are generally triggered by unequal power relations, domestic violence, economic injustice, and weak communication and fulfillment of rights within the family. A gender equality perspective positions this phenomenon not as a threat to the value of a harmonious family, but rather as a reflection of the need to reconstruct just, equal, and civilized marital relations. Therefore, PUSAKA SAKINAH needs to be developed adaptively by integrating the principles of gender equality, protecting women's rights, and strengthening the capacity of married couples to build relationships of mutual respect. Strengthening the educational and preventive dimensions of PUSAKA SAKINAH is expected to reduce the divorce rate and create harmonious, gender-equitable and sustainable families.